1998
DOI: 10.2116/analsci.14.535
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroelectrochemical Characterization of Some Polypyrrole/Anthraquinone Sulfonate Films

Abstract: Conducting polymer films incorporating electroactive species have been used for sensor applications, and the redox properties have been utilized in charge-storage devices such as super-capacitors and batteries. [1][2][3][4][5][6] The optical properties associated with redox switching in some conducting polymers have been studied for possible use in electrochromic devices with high coloration efficiencies.7-14 Polypyrrole (PPy) is one of the most useful conducting materials, since it polymerizes easily, forms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…We have previously investigated the complexation of 8-hydroxyquinoline-5-sulfonyl hydrazide with metal ions [22,23,24] and recently found that electrical conductivity, electroactivity, and spectroelectroactivity could be induced in poly(o-toluidine) and/or polypyrrole emeraldine base form after doping [25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated the complexation of 8-hydroxyquinoline-5-sulfonyl hydrazide with metal ions [22,23,24] and recently found that electrical conductivity, electroactivity, and spectroelectroactivity could be induced in poly(o-toluidine) and/or polypyrrole emeraldine base form after doping [25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(o-anisidine) doped with hydrochloric acid (HCl-doped POAN) was prepared following the previously described procedure [32][33][34]. The oxidation of o-AN in strong acid medium (HCl, 1.5 mol l −1 ) produces a radical cation, which can react with further molecule to give predominantly paralinked dimeric radical.…”
Section: Experimental Chemicals and Materialsmentioning
confidence: 99%
“…The problem of thermal stability of homo-and hetero-chain linear polymers has important applications [25][26][27]. In our previous work, we have found that the electrical conductivity, electroactivity, spectroelectroactivity or thermal stability could be induced into some polymeric forms [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…A pyrrole vs. AQS Ϫ ratio of 3:1 has been suggested for polypyrrole/AQS Ϫ films, 21,22 and a relative doping level of 78% (4:1) was calculated for our particles from results of elemental analysis. Perchlorate added on polymerization would occupy the rest of the position.…”
mentioning
confidence: 92%
“…21 Elemental analysis of PPyPVA(AQS Ϫ ) also indicated the inclusion of AQS Ϫ (percent found for sulfur, 4.0%). Consequently, we can safely conclude from the results of TG-MS, FT-IR, and elemental analysis that the PPyPVA particle was doped with AQS Ϫ and was highly hydrophilic.…”
mentioning
confidence: 99%